Analisis Risiko dalam Investasi Islam - Irkhami, Nafis (IAIN Salatiga, 2010)
Business activities and investments could not be separated from risk, becausethe return was a result of the risk analysis. Based on its nature, it was no small investment activities, especially in the field of financial assets, which in fact exploit the conditions in a way to speculate. In many cases, these speculators caused often create economic inequality, even crisis. This article would find footing construction investment ethical analysis of Islamic pespectives, including the instruments of the screening process, as well as the concept of Islamic investment analysis of risk and return.